Foliar Application of Salicylic Acid at Different Phenological Stages of Peach Fruit CV. ‘Flordaking’ Improves Harvest Quality and Reduces Chilling Injury during Low Temperature Storage - Irfan Ali; Xiukang Wang; Mohammad Javed Tareen; Fahad Masoud Wattoo; Abdul Qayyum; Mahmood Ul Hassan; Muhammad Shafique; Mehwish Liaquat; Sana Asghar; Tanveer Hussain; Sajid Fiaz; Waseem Ahmed (Plants, 2021)
Peaches are well-liked amongst the stone fruits in Pakistan. The peach industry faces significant losses, from harvesting to marketing. The objective of this study was to investigate the effectiveness of foliar sprays of salicylic acid (SA) on the fruit quality of peaches (cv. ‘Flordaking’) at the harvest and postharvest life or stages. Different concentrations of SA (control, 1, 2 and 3 mM) were sprayed on the plants at three growth stages of fruit, i.e., the cell division, cell enlargement and pit-hardening stages. In general, all the SA treatments improved the fruit quality at harvest and maintained higher levels of flesh firmness, titratable acidity and ascorbic acid during storage. However, fruit weight loss, soluble solid contents, membrane leakage, chilling injury, color development, disease and decay incidence and the climacteric peak of ethylene were lowered by SA treatment after six weeks of low-temperature storage. SA at a 3-mM concentration was proven to be the most effective in maintaining the quality for a longer period of time during low-temperature storage. Based on the results, it can be concluded that the application of SA at fruit development stages can improve the harvest quality and storability of ‘Flordaking’ peaches.